Strategy for Correction of the Whistling Deformity in Secondary Cleft Lip Reconstruction - Jian, Xinchun (Plast Reconstr Surg Glob Open, 2020)
BACKGROUND: Following primary repair of a cleft lip, patients present with many facial deformities. One of the commonly observed sequelae of cleft lip repair is a whistling deformity. This retrospective study was carried out to evaluate the outcomes following correction of whistling deformities in secondary cleft lip reconstruction. METHODS: We retrospectively reviewed the hospital records of patients with various whistling deformities who underwent repair from April 1989 to March 2018; 2 surgeons performed the repair using either the double movable mucomuscular complex flaps technique, modified Abbe flap technique, or Abbe flap technique. The postoperative anatomical structure and aesthetic effects of the surgery were evaluated. RESULTS: In total, 136 patients were included in this study. Among these patients, 60 (44.2%) had a grade I whistling deformity and 47 (34.5%) had a grade II deformity and repair was performed using the double movable mucomuscular complex flaps technique and modified Abbe flap transfer technique, respectively, whereas the Abbe flap transfer technique was used in 16 patients (11.8%) and 13 patients (9.5%) with a grade III and grade IV whistling deformity, respectively. All patients were found to have normal postoperative anatomical structures and aesthetic effects of the upper lip, with all patients experiencing mild to moderate postoperative edema of the upper lip, and 29 cases (21.3%) developed an inconspicuous scar. CONCLUSION: The repair technique should be chosen based on the type of whistling deformity.